Using unconventional wisdom to re-assess and rebuild the BRICS - Bertrand Guillotin (Journal of Risk and Financial Management, 2019)
In 2015, Goldman Sachs closed its BRIC (Brazil, Russia, India, China) fund after years of losses and plummeting assets. Emerging markets had, once again, turned into submerging markets. Their dependence on 'developed' markets and established institutions had failed them in a post-Global Financial Crisis (GFC) era, anchored in protectionism, risks, volatility, and uncertainty. The once commonly-accepted wisdom that called for US housing prices to always increase was part of the problem and contagion. Rebuilding the BRICS (S for South Africa) using conventional wisdom would probably not work. A new approach is necessary, especially since the last key contributions to show the inadequacy of a conventional wisdom-based strategy in emerging markets are more than ten years old. To help fill this gap, this paper proposes a holistic analytical framework for strategists to re-assess risks and opportunities in the BRICS. We illustrate how five basic assumptions can be proven wrong and lead to the creation of unconventional wisdom that can help derive some strategic insights. We find that rebuilding the BRICS for them to be more resilient is possible, if not vital, for the health of the global economy.
Keywords: 330; emerging markets; globalization; protectionism